The most problematic symptoms of prion disease – an analysis of carer experiences. (August 2019) - Ford, Liz; Rudge, Peter; Robinson, Kathy; Collinge, John; Gorham, Michele; Mead, Simon
ABSTRACT: Objectives: Prion diseases are rare dementias that most commonly occur sporadically, but can be inherited or acquired, and for which there is no cure. We sought to understand which prion disease symptoms are most problematic for carers, to inform the development of outcome measures. Design: Self-completed questionnaire with follow-up of a subset of participants by structured interview. Setting: A nested study in the UK National Prion Monitoring Cohort, a longitudinal observational study. Participants and measurements: 71 carers, of people with different prion diseases with a wide range of disease severity, identified 236 of their four most problematic symptoms by questionnaire which were grouped into ten domains. Structured interviews were then done to qualitatively explore these experiences. Eleven family carers of people with prion disease were selected, including those representative of a range of demographics and disease subtypes and those who cared for people with prion disease, living or recently deceased. Interviews were transcribed and formally studied. Results: The six most problematic symptom domains were: mobility and coordination; mood and behavior; personal care and continence; eating and swallowing; communication; and cognition and memory. The prevalence of these symptoms varied significantly by disease stage and type. A formal analysis of structured interviews to explore these domains is reported. Conclusions: We make suggestions about how healthcare professionals can focus their support for people with prion disease. Clinical trials that aim to generate evidence regarding therapies that might confer meaningful benefits to carers should consider including outcome measures that monitor the symptomatic domains we have identified as problematic.